An Unexpectedly High Number of New Sutorius (Boletaceae) Species From Northern and Northeastern Thailand - Vadthanarat, Santhiti; Halling, Roy E.; Amalfi, Mario; Lumyong, Saisamorn; Raspé, Olivier (Frontiers in Microbiology, 2021)
Sutorius is a poroid genus in Boletaceae that typically has chocolate brown to reddish brown or purplish brown basidiomata with a finely scaly stipe and produces a reddish-brown spore deposit. During the survey on diversity of boletes in Northern and Northeastern Thailand, several Sutorius collections were obtained. Combined evidence from morphology and phylogenetic analyses of a three-gene data set (atp6, tef1 and rpb2) of the Sutorius collections along with selected Boletaceae in the Pulveroboletus group indicated that Thai collections represent seven new Sutorius species. The analyses also indicated that Tylopilus maculatoides belongs in Sutorius. Therefore, the transfer of T. maculatoides to Sutorius is proposed. Full descriptions, illustrations of the seven new species and S. maculatoides are presented in this study. With the seven new species and the new combination, eight of the eleven described Sutorius species are known to occur in Northern and Northeastern Thailand, while only one species are known from each of two continents, the Americas and Australia.